The enchanted castle - Nesbit, E. (Usborne Pub Ltd; UK, 2007)
A re-telling of the classic E.Nesbit story for children growing in reading confidence. The Enchanted Castle tells the story of Jerry, Jimmy and Cathy, three children who discover a magical castle occupied by an invisible princess, and enter a world full of magic and adventure. Evocatively illustrated by Alan Marks. Usborne Young Reading has been developed with reading experts from Roehampton University.